Enhanced phycocyanin and protein content of Arthrospira by applying neutral density and red light shading filters: a small‐scale pilot experiment. Issue 6 (8th April 2019) - Kilimtzidi, Evmorfia; Cuellar Bermudez, Sara; Markou, Giorgos; Goiris, Koen; Vandamme, Dries; Muylaert, Koenraad
Abstract: BACKGROUND: The cyanobacterium Arthrospira contains proteins and the blue pigment phycocyanin that can be used as a natural colourant in the food industry. The aim of this study was to investigate a strategy for increasing the yield of phycocyanin and protein from Arthrospira cultures by shading the cultures with neutral density and red light filters. Experiments were conducted under three different irradiance conditions: (i) laboratory tests under relatively low light intensities (100 μmol m −2 s −1 ), (ii) laboratory tests under relatively high light intensities (516 μmol m −2 s −1 ) and (iii) scaled‐up tests under natural conditions by cultivating Arthrospira in raceway ponds in a greenhouse. RESULTS: In all cases, shading of cultures with red filters resulted in biomass with increased phycocyanin content achieving a maximum of 134, 71 and 121 mg g −1 under low light intensity, high light intensity and natural conditions, respectively. Under high light intensity and natural conditions, shaded cultures displayed phycocyanin of higher purity and increased protein content, which reached up to 43 and 65%, respectively. CONCLUSIONS: Shading of Arthrospira cultures by low‐cost polyester red light filters may be an effective way for enhancing phycocyanin production and improving its purity in outdoor 'spirulina farms'. © 2019 Society of Chemical Industry